Benefits of an early management of palpitations. Issue 28 (July 2018) - Clementy, Nicolas; Fourquet, Ambroise; Andre, Clémentine; Bisson, Arnaud; Pierre, Bertrand; Fauchier, Laurent; Babuty, Dominique; Angoulvant, Denis
Abstract : Abstract: Palpitations are a frequent symptom in the general population, and if cardiac arrhythmias are the most frequent etiology, their diagnosis may be uncertain. We sought to see whether a specialized management of palpitations is associated with a high diagnostic accuracy in patients presenting with palpitations. Consecutive patients addressed for isolated palpitations in our outpatient cardiac unit were prospectively included in this observational cohort study. The initial management was standardized: 12-lead electrocardiogram (ECG) as early as possible, ECG monitoring, potentially followed by an individualized management. On 688 consecutive patients prospectively included, cardiac arrhythmia as the cause of palpitations was found in 81% of cases (77% of atrial arrhythmias, 15% of junctional tachycardia, and 8% of ventricular arrhythmias). A total of 96% of diagnoses were made during initial management. Prehospital ECG (92%) and ECG at admission (67%) had the best positivity rates. A specialized management of patients presenting with lone palpitations allows the diagnostic of a cardiac arrhythmia in >80% of cases. Earliness of an ECG recording remains the key element in the diagnostic approach of these patients.